Discrepancies between Female Student Perception and Reality of the Engineering Industry - Keen, Julia; Salvatorelli, Anna (My University, 2017)
Demographic trends predict a shortage of engineers, with women being one group targeted to fill this gap. Although the percentage of engineering degrees attained by women has increased, there has not been an equal increase in the number of women working in the industry. This means that women are either leaving the industry after they enter or not entering at all. The purpose of this study was to identify what can be done in the education of female engineering students to better prepare them for the engineering workforce reality and culture. A survey was conducted to collect information from female architectural engineering students about their perception of the industry. The results were then compared to the actual conditions of the workforce. The goal was to identify areas of discrepancy between perception and reality so that these areas can be addressed before students enter the workforce. The hope is that, with a better understanding of their career environment, women will be better prepared to deal with the issues that may cause them to leave the industry.
Citation: Julia Keen, & Anna Salvatorelli. (2016). Discrepancies between Female Student Perception and Reality of the Engineering Industry. https://doi.org/10.1061/(ASCE)AE.1943-5568.0000221
Keywords: Architectural Engineering; Employees; Data Collection; Women; Industries; Engineering Education